Discovery of an Aedes (Stegomyia) albopictus population and first records of Aedes (Stegomyia) aegypti in Canada. Issue 1 (30th September 2019) - Giordano, B. V.; Gasparotto, A.; Liang, P.; Nelder, M. P.; Russell, C.; Hunter, F. F.
Abstract: A population of Aedes ( Stegomyia ) albopictus (Skuse) (Diptera: Culicidae), a vector of chikungunya, dengue, yellow fever, and Zika and West Nile viruses, has been detected in Windsor, Ontario, Canada from 2016 onwards. Here, we describe its seasonal distribution, as well as the various aquatic habitats from which this species was collected and its larval co‐habitation. We collected immatures from tires, treeholes, extruded polystyrene foam containers, discarded plastic cups, old recycling bins and oviposition traps. Aedes albopictus larvae were collected with Aedes japonicus (Theobald), Anopheles punctipennis (Say), Culex pipiens Linnaeus, Ochlerotatus hendersoni (Cockerell), Ochlerotatus triseriatus (Say) and Orthopodomyia signifera (Coquillett). Adult female and male specimens were collected from Biogents sentinel traps (Biogents AG, Regensburg, Germany), as well as Centers for Disease Control and Prevention miniature light traps (CDC, Atlanta, GA, U.S.A.), and also as they alighted on the investigators. Peak adult collections occurred in September during epidemiological week 37. We also collected Aedes ( Stegomyia ) aegypti (Linnaeus), a new record for Canada, in 2016 and from two new collection sites in 2017. The 2017 collections were 3.5 km north and 19.4 km south of the index site. The present study adds to the increasing number of studies reporting range expansions of these mosquito species. Abstract : Aedes albopictus has established a population in the southern Ontario city of Windsor, located directly across from Detroit, Michigan, on the southern shore of the Detroit River. Aedes albopictus were not readily captured in Centers for Disease Control and Prevention miniature light traps and larvae were found in a variety of man‐made and natural containers with native container‐breeder species. In the present study, we collected specimens of Aedes aegypti (a new record for Canada) in 2016 and 2017 at multiple sites.